PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 012 BASILAM BARU - Roskariyawani '; Munjiatun '; Mahmud Alpusari Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is motivatedby low, yields graders learn science IV SD NEGERI 012 Basilam Baru Dumai. Therefore, teeachers use a variety of learning models to improve student learning outcomes. Problem of this study is whether the application of the learning model cooperative Numbered Head Together (NHT) can improve student learning outcomes IPA class IV SD NEGERI 012 Basilam Baru Dumai? These studies aim to improve student learning outcomes IPA class IV SD NEGERI 012 Basilam Baru Dumai whit material resources. The research desigh ig an action research (PTK) who performed a total of two cycles consist of the meeting there were two meeting and one-time daily tests. And of research activity teacher observations obtained at the first meeting 60,71% category enough, the second meeting 71,41% categories withan increase of 17,64%, the third meeting of 78,57% both categories increased by 18,17%. Furhermore, observations of student activity at the first meeting 50% categoty is less, at the second meeting 60,71% category enough. An increase of 21,42% , the third meeting 82,14% either categori, an increase of 8,59%. In cycle i result replicates the resuls of an average of 73,89% increased 20,93%.cycle test results 83,33% also increased by 12,77%. Thus from this study it can be cancluded that the application of the learning model cooperative Numbered Head Together (NHT) can improve student learning outcomes IPA class IV SD NEGERI 012 Basilam Baru Dumai. Key Words: model learning Numberad Head Together (NHT)